A global high resolution coastline database from satellite imagery - Sanduni D. Mudiyanselage; Chunli Dai; Ian M. Howat; Eric Larour; Erik Husby (Scientific Data)
Abstract In this dataset, we present global coastlines, water probability maps, and intertidal zones derived from a large collection of multispectral images acquired by Maxar (formerly DigitalGlobe) satellites between 2009 and 2023. The extracted coastlines correspond to the median tidal height of all image acquisitions at a location, with the modeled tidal height included in the product. These products are provided at a high spatial resolution of 2 m across the globe. Coastline products are compared with the standard coastline products from NOAA. The water probability and coastline data are used to generate coastal intertidal zones, which represent the horizontal extent water covers during the transition between low tide and high tide. Intertidal zones are dynamic regions that could be recognized as sensitive coastal areas to sea level variations. We detect the largest intertidal zone in south-central Alaska, with a total area of 124.7 km2 and a width of 3.8 km. The high resolution coastline product can support coastal resources management and planning and coastline changes corresponding to sea level rise.